Boosted tidal disruption by massive black hole binaries during galaxy mergers from the view of n-body simulation - Li, Shuo; Berczik, Peter; Spurzem, Rainer (The astrophysical journal, 2017)
Supermassive black hole binaries (SMBHBs) are productions of the hierarchical galaxy formation model. There are many close connections between a central SMBH and its host galaxy because the former plays very important roles on galaxy formation and evolution. For this reason, the evolution of SMBHBs in merging galaxies is a fundamental challenge. Since there are many discussions about SMBHB evolution in a gas-rich environment, we focus on the quiescent galaxy, using tidal disruption (TD) as a diagnostic tool. Our study is based on a series of numerical, large particle number, direct N -body simulations for dry major mergers. According to the simulation results, the evolution can be divided into three phases. In phase I, the TD rate for two well separated SMBHs in a merging system is similar to that for a single SMBH in an isolated galaxy. After two SMBHs approach close enough to form a bound binary in phase II, the disruption rate can be enhanced by ∼2 orders of magnitude within a short time. This “boosted” disruption stage finishes after the SMBHB evolves to a compact binary system in phase III, corresponding to a reduction in disruption rate back to a level of a few times higher than in phase I. We also discuss how to correctly extrapolate our N -body simulation results to reality, and the implications of our results to observations.